Narrating Arabic Reading in the Digital Age: A Narrative Inquiry into Generation Alpha Learning in Indonesian Pesantren - Abdurrahman Abdurrahman; Zulfan Syakhansyah; Naser Ali Abdulghani (International Journal of Educational Narratives, 2026)
Background: Traditional linear Arabic language instruction in Indonesian Islamic boarding schools (pesantren) faces a cognitive mismatch with Generation Alpha. Although technology has been adopted, current literature has not yet explored how students’ subjective experiences bridge classical texts with their digital cognitive habits. Objective: This study aims to explore the learning experience narratives of teachers and students in implementing a pedagogical framework that bridges classical Arabic texts with the visual-digital logic of the contemporary generation. Methods: This research employs a qualitative case study design with a narrative approach. Data were collected through participant observation and in-depth interviews with four students and two teachers. The thematic analysis method by Miles, Huberman, and Saldaña was utilized to deconstruct the flow of subjects’ experiences and reflections. Results: The study reveals that Generation Alpha possesses a dominant intuitive-visual literacy inclination in processing information. Participant narratives indicate that the “creative-hybrid bridge” strategy, which integrates digital aesthetics into classical texts, successfully transformed the learning experience from passive rote memorization into active, game-based discovery. The findings highlight an enrichment in reading comprehension quality and the growth of learner autonomy rooted in the synchronization of materials with the students’ visual logic. Conclusion: The proposed pedagogical interface model provides a theoretical contribution to digital language pedagogy within traditional environments. This model proves that integrating digital cognitive architecture into classical materials can sustain linguistic traditions without losing substantive depth for future generations.